Unpacking the Possibilities of a Vernacular Language Archive (Journal of the Digital Humanities Association of Southern Africa, 2023)
The Five Hundred Year Archive is a research project of the Archive and Public Culture Research Initiative based at the University of Cape Town. In an effort to stimulate greater engagement with the deep southern African past, the project has created a corpus of vernacular resources ranging from the earliest available to 1910. It includes productions by an array of African intellectuals in a host of African languages. The vernacular corpus, with its rich metadata, constitutes an extended language and conceptual archive. It is useful to historians, but may also offer research possibilities in other fields, particularly if used in conjunction with contemporary computational methods.
Keywords: African Intellectuals; Vernacular Writing; Orthography; Metadata; Copyright